Haunting and the ghostly matters of undefined illness - Overend, Alissa (My University, 2014)
The concept of haunting has become common parlance in the humanities and social sciences (Derrida, 1994; Gordon, [1997]2008; Gunn, 2006; Rosenberg, 2010; Roseneil, 2009; Saltmarsh, 2009). What I find curious, and ultimately take up in this article, is the near-virtual absence of the concept of haunting within critical studies on health, illness and the body. Following the work of cultural theorist Avery Gordon [1997]2008, I question what can be learned about the workings of undefined illness by attending to what she frames as ‘ghostly matters’ – the liminal spaces of social life. I use the case of Candida – a yeast-related disorder of vague symptomatology – to speak to the experiences of bodily uncertainty, and to the symptoms of illness which are neither wholly present nor wholly absent. I contend that what is missing in the case of Candida is not simply an empirical diagnosis, but an ability to account for all those illness experiences that fall outside biomedicine approaches to the sign, symptom and pathology of illness. It is precisely because of the empirical truths put forth by biomedicine that Candida comes to exist (and be experienced) as a bodily certainty of the barely visible, as a possessive force consuming the body it inhabits, and as a specter of death haunting positivist ideals of bodily certainty.
Keywords: haunting; undefined illness; Candida; yeast-related disorder; bodily uncertainty; biomedicine; symptoms of illness; bodily certainty; bodily certainty; illness experiences